Evaluation Of Novel Opioid-Sparing Techniques To Reduce Postoperative Pain (The Review of Diabetic Studies, 2025)
Background: Postoperative pain management has traditionally relied on opioids, which carry significant risks of adverse effects and long-term dependence. This has prompted the exploration of novel opioid-sparing techniques to provide effective analgesia while minimizing opioid exposure. This study aimed to evaluate the effectiveness of a multimodal opioid-sparing protocol in reducing postoperative pain and opioid consumption.Methods: A prospective, comparative study was conducted with 120 patients undergoing elective surgery. Participants were randomly assigned to either an opioid-sparing intervention group (n=60) or a conventional opioid-based control group (n=60). The intervention group received a tailored multimodal protocol combining pharmacological agents (e.g., NSAIDs, acetaminophen, gabapentinoids), regional anesthesia, and non-pharmacological interventions. Primary outcomes included postoperative pain intensity measured on a visual analog scale (VAS) and opioid consumption recorded in morphine milligram equivalents (MME).Results: The opioid-sparing group demonstrated significantly lower pain scores at all measured time points (e.g., immediate postoperative VAS: 3.2 vs. 5.6, p